4-Chloro-N-(3-methoxyphenyl)benzamide - Roderick G. Stanley; Jim Simpson; Naeem Abbas; Rasheed Ahmad Khera; Aamer Saeed (Acta Crystallographica Section E, 2008)
The title benzamide derivative, C14H12ClNO2, crystallizes with two independent molecules in the asymmetric unit. Both are close to being planar, with dihedral angles between the two benzene rings of 11.92 (6) and 12.80 (7)°. In the crystal structure, N—H...O hydrogen bonds link molecules into chains along a. These interactions are augmented by C—H...O hydrogen bonds to form two-dimensional layers in the ac plane. Additional C—H...O interactions result in a three-dimensional network consisting of undulating rows along c. The crystal studied was an inversion twin with a 0.59 (3):0.41 (3) domain ratio.